2021
DOI: 10.3390/ma14195761
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Caking Coatings for Improving the Useful Properties of Ammonium Nitrate Fertilizers with Composition Modeling Using Box–Behnken Design

Abstract: Granular fertilizers (especially those based on ammonium nitrate (AN)) tend to agglomerate during storage. The aims of this research were to develop effective anti-caking coatings for ammonium nitrate fertilizers while improving the quality of fertilizers and to optimize the composition of effective anti-caking coatings. The influence of the composition of the prepared organic coatings on the effectiveness of preventing the caking of fertilizers was studied by response surface methodology (RSM) using Box–Behnk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Moreover, we could not define a relationship between anticaking efficiency (%DC) and CS values. Tyc et al 38 and Cemre et al 46 reported that the CS values improved after the fertilizers were treated with oil‐based commercial anticaking agents, reducing caking. However, we could not improve the CS value of 15‐7‐18 or 18‐4‐5 by treatment with our designed anticaking agents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we could not define a relationship between anticaking efficiency (%DC) and CS values. Tyc et al 38 and Cemre et al 46 reported that the CS values improved after the fertilizers were treated with oil‐based commercial anticaking agents, reducing caking. However, we could not improve the CS value of 15‐7‐18 or 18‐4‐5 by treatment with our designed anticaking agents.…”
Section: Resultsmentioning
confidence: 99%
“…Response Surface Methodology (RSM) with Box–Behnken Design (BBD) was used to investigate the effects of three independent parameters (i.e., polymer, surfactant, and solvent contents) on anticaking performance. RSM considers all aspects among linear, square parameters and their interaction operating at three different levels providing accurate optimization results 37,38 . Comparing with a classical optimization method (one‐variable‐at‐a‐time), the RSM includes several parameters at a time, resulting in less number of experiment trials 39 .…”
Section: Introductionmentioning
confidence: 99%
“…The Box–Behnken design (BBD) is a common method of prescription process optimization, and it has obvious advantages in the process of prescription optimization. It can consider the linear and square effects of the changes in the values of the independent variables and the influence of their linear interactions [ 34 , 35 ]. The NS is a thermodynamically unstable system.…”
Section: Introductionmentioning
confidence: 99%
“…In all production methods of ammonium nitrate, chemicals are added to limit its moisture sorption properties (Gezerman, 2021). The chemical used to limit the hygroscopic properties of ammonium nitrate is not a preferred method by manufacturers due to the cost problem (Tyc et al, 2021;Tyc et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The production process of ammonium nitrate consists of the reaction of anhydrous ammonia and nitric acid, the evaporation way of the water in the content of ammonium nitrate, which has a concentration of around 70-80%, and the addition of anti-caking chemicals in order to limit the moisture absorption capacity by granulating it after it reaches 99% concentration (Hong et al, 2020;Chen et al, 2019). The bulk conditions of ammonium nitrate subjected to the storage process after such a production process can be considered as the most important parameter affecting the physical characterization of ammonium nitrate (Afrassiabian et al, 2019;Tyc et al, 2021).…”
Section: Introductionmentioning
confidence: 99%